2022
DOI: 10.1186/s12870-022-03460-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of Tomato Golden 2-Like transcription factors and abiotic stress related members screening

Abstract: Background Golden 2-Like (G2-like) transcription factors play an important role in plant development. However, the roles of these G2-like regulatory genes in response to abiotic stresses in tomato are not well understood. Results In this study, we identified 66 putative G2-like genes in tomato (Solanum lycopersicum) and classified them into 5 groups (I to V) according to gene structure, motif composition and phylogenetic analysis. The G2-like genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 97 publications
2
23
0
Order By: Relevance
“…In this study, 40 EgrGLK genes were identified in the E. grandis genome ( Supplementary Table S2 ). The number of EgrGLK genes was less than the number of GLK genes identified in Arabidopsis (55), maize (59), and tomato (66) ( Liu et al, 2016 ; Alam et al, 2022 ; Wang et al, 2022 ). It was suspected that some EgrGLK genes were lost during evolution ( Du et al, 2022 ).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In this study, 40 EgrGLK genes were identified in the E. grandis genome ( Supplementary Table S2 ). The number of EgrGLK genes was less than the number of GLK genes identified in Arabidopsis (55), maize (59), and tomato (66) ( Liu et al, 2016 ; Alam et al, 2022 ; Wang et al, 2022 ). It was suspected that some EgrGLK genes were lost during evolution ( Du et al, 2022 ).…”
Section: Discussionmentioning
confidence: 82%
“…To identify the GLK genes of E. grandis , genomic data were downloaded from the Phytozome database. 1 Using published GLK protein sequences from Arabidopsis , maize, and tomato as query sequences ( Liu et al, 2016 ; Alam et al, 2022 ; Wang et al, 2022 ), the GLK protein sequences in the E. grandis reference genome were identified with the BLASTP tool ( E -value: 1e −5 ). The identified sequences were submitted to the SMART online tool 2 and the NCBI Web CD-Search Tool 3 for further confirmation of GLK proteins.…”
Section: Methodsmentioning
confidence: 99%
“…The GLK transcription factor, which is a member of the newly classified GARP superfamily [ 14 ], plays an essential role in the formation and development of chloroplasts [ 11 , 47 ]. As reported in previous studies, detailed features and functions of GLK genes have been uncovered in Arabidopsis [ 6 ], maize [ 22 ], tobacco [ 24 ], and tomato [ 23 ]. However, little was known about the members of the moso bamboo GLK family until now.…”
Section: Discussionmentioning
confidence: 94%
“…Moso bamboo ( Phyllostachys edulis ) is a rapidly growing forest product that is widely used to manufacture paper, art ware, and food resources, with multiple economic, ecological, and cultural values in China and many other countries, sees a possibility for gene identification and function analysis that will help with it contributing on an even wider spectrum with the completion of the genome sequence [ 6 , 20 , 21 ]. The GLK gene family, previously identified and described within certain plants, for example, maize [ 22 ], Arabidopsis [ 6 ], tomato [ 23 ], and tobacco [ 24 ]. However, there are scarcely any reports on the characteristics and functions of GLKs in Phyllostachys edulis .…”
Section: Introductionmentioning
confidence: 99%
“…Salinity stress is one of the major abiotic stresses limiting plant growth and productivity, it also suppresses the growth of S. polyrhiza [ 60 ]. There are many reports of the GARP genes that responded to salt stress, such as AtGLK2/5/8/20/23/26/34/43/46 in A. thaliana [ 11 ], ZeGLK3 in Z. mays [ 43 ], 27 SiGLK genes in S. lycopersicum [ 61 ], and GhGLK55/120 in G. hirsutum [ 40 ]. In our study, we found that the expression of SpGLK25 was downregulated under salt stress, which helps to explain why the salt stress affects N/P uptake, and growth rate in plants [ 60 ].…”
Section: Discussionmentioning
confidence: 99%